Aktivitas Antioksidan AKTIVITAS ANTIOKSIDAN DARI EKSTRAK ETANOL KULIT BATANG SUKUN (Artocarpus altilis (Parkinson ex F.A.Zom) Fosberg : AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL KULIT BATANG SUKUN (Artocarpus altilis (Parkinson ex F.A.Zom) Fosberg - Syilfia Hasti; Raoda makbul (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2022)
Artocarpus altilis (Parkinson ex F.A.Zom) Fosberg is also widely used in traditional medicine. People living in Indonesia, use the fruit flesh as a tonic for the liver and use decoction of the leaves to treat to treat liver cirrhosis, hypertension, and diabetes. Research has been done on antioxidant activity using DPPH method on ethanol extract of breadfruit bark (Artocarpus altilis (Parkinson ex F.A.Zom) Fosberg using 2-Diphenyl-1-picrylhydrazyl as a free radical. Antioxidant activity test with comparison of vitamin C. The parameter measured is the absorbance using a 96 well Microplate Reader (Epoch®), then the IC50 value is calculated. This study aimed to determine the antioxidant activity of the ethanolic extract of the breadfruit (Artocarpus altilis (Parkinson ex F.A.Zom) stem bark extract. The antioxidant test results of the ethanol extract of breadfruit stem bark (Artocarpus altilis (Parkinson ex F.A.Zom) Fosberg had an IC50 value of 133.98 µg/mL with the medium category.